2018
DOI: 10.1111/iju.13574
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of the pretreatment aspartate transaminase/alanine transaminase ratio in patients treated with first‐line systemic tyrosine kinase inhibitor therapy for metastatic renal cell carcinoma

Abstract: Our findings show that the pretreatment De Ritis ratio can provide valuable information about the survival outcomes of metastatic renal cell carcinoma patients receiving first-line tyrosine kinase inhibitor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
0
29
1
Order By: Relevance
“…Initially identi ed 267 articles through the search strategy, 19 studies remained after removing duplicates and excluding articles by viewing titles and abstracts. Based on corresponding inclusion and exclusion criteria, 8 articles comprising 5,025 patients were nally included in the present study [14,15,[18][19][20][21][22][23] ( Figure 1). All studies had a retrospective design, two of which were propensity score-matched analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially identi ed 267 articles through the search strategy, 19 studies remained after removing duplicates and excluding articles by viewing titles and abstracts. Based on corresponding inclusion and exclusion criteria, 8 articles comprising 5,025 patients were nally included in the present study [14,15,[18][19][20][21][22][23] ( Figure 1). All studies had a retrospective design, two of which were propensity score-matched analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…3 studies focused on metastatic RCC [19,21,22], 5 studies focused on non-metastatic RCC [14,15,18,20,23]. These studies were conducted in ve countries, including China, Korea, Turkey, Japan, and the United States.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In this issue of the International Journal of Urology , Kang et al . showed the usefulness of the De Ritis ratio as a predictive marker in metastatic RCC patients who received first‐line systemic targeted therapy . Patients with a higher pretreatment De Ritis ratio (≥1.2) had worse CSS and OS outcomes, compared with those with a lower De Ritis ratio (<1.2).…”
mentioning
confidence: 98%
“…A potential weak point of these criteria is that a relatively high number of patients are classified into the intermediate‐risk group. The application of the De Ritis ratio, using stratification by above or below 1.2 (AST/ALT), resulted in populations with distinctly separate CSS and OS outcomes in the intermediate‐risk group, although no significant effect was found on survival outcome among the patients in the favorable and poor risk groups . The AST and ALT levels can be easily evaluated and monitored routinely without invasive procedures.…”
mentioning
confidence: 99%
“…Kang et al . reported the prognostic impact of the aspartate transaminase (AST)/alanine transaminase (ALT) ratio, referred to as the De Ritis ratio, in metastatic renal cell carcinoma (mRCC) patients treated with first‐line systemic tyrosine kinase inhibitor . Their study showed that patients with a higher De Ritis ratio had worse cancer‐specific survival and overall survival than those with a lower ratio.…”
mentioning
confidence: 99%